Delphinidin-3-glucoside prolongs lifespan and healthspan in Caenorhabditis elegans with and without environmental stress - John Sylvester B. Nas, Paul Mark B. Medina (Journal of Applied Pharmaceutical Science, 2024)
The beneficial effects of crude anthocyanin extracts against ageing, cancer, and bacterial infections are widely documented in the literature. Delphinidin-3-glucoside (D3G) is a class of anthocyanin pigment in fruits and vegetables. Although there are in vitro studies on the bio-functional activities of D3G, none are in vivo. Thus, we examined the effects of D3G on the lifespan of Caenorhabditis elegans (C. elegans) and measured the healthspan indicators like egg-laying ability and pharyngeal pumping during its normal state and in the presence of stressors, such as heat, ultraviolet (UVA) light, and hydrogen peroxide (H2O2). We found out that D3G prolongs the lifespan and improves its health span without stress. These same effects were observed with oxidative stress but not heat and UVA stressors. D3G partially reverses the adverse effects of H2O2 by prolonging the lifespan and augmenting the pharyngeal pumping of treated C. elegans, albeit lower than untreated. Overall, our findings suggest that D3G is capable of extending the lifespan and improving health through its antioxidant properties.
Keywords: Delphinidin-3-glucoside, anthocyanin, aging, lifespan, healthspan, Caenorhabditis elegans